EFFECTS OF ILLICIT DRUG CONSUMPTION ON ORAL HEALTH AND QUALITY OF LIFE: A NARRATIVE REVIEW - Alice Murariu; Livia Bobu; Simona Stoleriu; Diana Zapodeanu; Lorena Morărașu; Elena Raluca Baciu (Romanian Dental Association for Education, 2024)
We have lately noticed an increase of illegal drug consumption among young people. This phenomenon is associated to acute and chronic health problems worsened by diverse factors such as the properties of substances, the way of administration, the vulnerability of the individual and the social context in which drugs are used. Drugs affect general health by causing psychiatric disorders, cardiovascular and neurological diseases and, in the case of high quantities, even coma and death. These substances inevitably have effects on the oral cavity from rampant caries, severe xerostomia to periodontal disease, perforation of the nasal septum and palate, and to leukoplakia and oral cancer. From the viewpoint of dental treatment, we must envisage an interdisciplinary approach with the psychiatrist, psychologist and internist. The quality of life of these individuals is impaired due to the impact of these substances not only on their health but also on the psychological side through the appearance of emotional, mental and social disorders represented by marginalization and the lack of integration into society. Among the illicit drugs, alcohol and marijuana are less damaging for health as compared to cocaine and crack cocaine which may result in serious and sometimes lethal diseases.